Rare case of Auto immune haemolytic anaemia in an infant with auto "f & kidd antibodies". (August 2020) - Gupta, Anubhav; Pokhrel, Anupa; Sachdeva, Prerna; Varshney, Shilpi; Arora, Harkiran; Chaudhary, Kiran; Asati, Swati
Abstract: Background: "f" antigen is a compound antigen in Rh blood group system. Anti f has haemolytic potential as described in literature. Its occurrence in an infant as autoantibody with another blood group system ie Jka is very rare. Case report We report a case of 10-month-old infant diagnosed with AIHA with autoantibodies directed towards "f" and Jka antigen. Antibody identification was done and antigen negative blood units were crossmatched & transfused with demonstrable haemoglobin rise and subsequent decrease in DAT grading. Result: Auto anti f + Jka was identified in a 10 months old infant. Autoantibodies were identified by identification 3 & 11 cell panel and select cell panel. Results were later confirmed by allogenic adsorption & elution. Patient was transfused antigen negative blood unit which lead to haemoglobin rise & gradual decrease in direct coombs test grading Conclusion: To our knowledge, this is the first case report of auto anti f + Jka having haemolytic potential in an infant which shows the importance of extensive immmunohaematology workup in providing compatible blood unit in patients with autoantibody.